2016
DOI: 10.1088/1748-0221/11/07/t07001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strong solenoidal focusing on beam emittance of low-energy intense proton beam in the SARAF LEBT

Abstract: Influence of strong solenoidal beam focusing on beam emittance was studied at the SARAF LEBT beam line using 5 mA 20 keV proton quasi-DC beams. The measurements show that within the experimental uncertainties, emittance does not change over the whole focusing range. Detailed beam dynamics simulations were performed to achieve better understanding of the experimental results. The experimental and simulation results are fully consistent with the assumption of nearly full space charge neutralization for the quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Measured beam current after the bending magnet is 7 mA and higher. Typical rms normalized emittance measured in the slit and wire apparatus, about one meter upstream of the RFQ is x;y;100%=0.15 •mm•mrad [5]. The beam is strongly focused towards the RFQ entrance by the third LEBT solenoid.…”
Section: Ecr Ion Source and Lebtmentioning
confidence: 99%
See 1 more Smart Citation
“…Measured beam current after the bending magnet is 7 mA and higher. Typical rms normalized emittance measured in the slit and wire apparatus, about one meter upstream of the RFQ is x;y;100%=0.15 •mm•mrad [5]. The beam is strongly focused towards the RFQ entrance by the third LEBT solenoid.…”
Section: Ecr Ion Source and Lebtmentioning
confidence: 99%
“…It was shown that the beam reaches high space-charge neutralization along the LEBT, which reduces de-focusing. Nevertheless, the beam's rms emittance increases to an estimated value of about 0.20 •mm•mrad at the RFQ entrance, due to an increased space charge force and leakage of the RFQ RF field [5].…”
Section: Ecr Ion Source and Lebtmentioning
confidence: 99%
“…At present we attempt to reproduce the effect with simulation. A detailed report on this work is in preparation [13].…”
Section: Selected Lebt Beam Studiesmentioning
confidence: 99%
“…Of particular concern was the rising edge of the beam pulse, which is susceptible to optical modifications due to beam neutralization buildup. The duration of the rising edge was estimated to be a fraction of a millisecond for the SARAF LEBT [9]. A comparison of the phase space distribution results between 5 mA DC beam and 5 ms chopped beams is presented in table 2.…”
mentioning
confidence: 99%